Assessment of spectrum value: application to sub-1GHz frequency bands - Carlos González-Valderrama; Zoraida Frías; Jorge Pérez Martínez (International Telecommunications Society (ITS), 2015)
This paper is focused on the impact in network operator costs of new sub-1GHz spectrum bands, which will be soon available to provide mobile broadband services. To analyse these effects a techno-economic model has been used to evaluate the maximum inter-site distance and therefore the cheapest network. The results achieved show the different value of the sub 1GHz bands depending on the spectrum holding of the operator.
Keywords: 330; Techno-economic model; digital dividend; second digital dividend; LTE